2006
DOI: 10.1182/blood-2006-09-046128
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell–derived TNF can promote Th17 cell–dependent neutrophil recruitment in ovalbumin-challenged OTII mice

Abstract: IntroductionSeveral proinflammatory cytokines, including TNF, IL-1, and IL-17, can directly induce neutrophil recruitment. For example, inhalation of recombinant TNF, IL-1, or IL-17 can provoke neutrophil infiltration into the airways. [1][2][3] These cytokines can also play important roles in the pulmonary neutrophilia induced by infection with the Gram-negative bacteria Klebsiella pneumoniae, and can contribute to bacterial clearance. [4][5][6] However, both the roles of these proinflammatory cytokines, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 54 publications
2
124
2
1
Order By: Relevance
“…Some of the positive immunomodulatory functions of mast cells that have been proposed based on in vitro studies have been confirmed in vivo using mast cell knock-in mice 1,54,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] or in mice lacking specific mast-cell-associated proteases [26][27][28][32][33][34] or lacking specific protease enzymatic activity 11 (Table 1 ). In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 .…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 93%
See 2 more Smart Citations
“…Some of the positive immunomodulatory functions of mast cells that have been proposed based on in vitro studies have been confirmed in vivo using mast cell knock-in mice 1,54,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] or in mice lacking specific mast-cell-associated proteases [26][27][28][32][33][34] or lacking specific protease enzymatic activity 11 (Table 1 ). In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 .…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 93%
“…In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 . Many of these studies also demonstrated that the lack of mast cells 54,[57][58][59][60][61][62][63][64]67,69,70 or a specific mast-cell product 28,32,33,54,60,63,67,68,70 also reduced the pathology associated with the immune response or impaired its effectiveness in promoting host resistance to infection.…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…101 They also influence T cell differentiation: IL-4 and histamine direct Th 2 responses 102 as well as modulate the differentiation of Th17 ϩ CD4 cells. 103 It is in the generation of effector responses, however, where mast cells may have the greatest impact. Mast cells in the periphery enhance effector T cell recruitment directly by the production of chemoattractants.…”
Section: Role Of Mast Cells In Inflammatory and Autoimmune Kidney Dismentioning
confidence: 99%
“…The adhesion molecules on mast cells, especially ICAM-1, can interact with T cells leading to T cell activation, but on the other hand mast cells can also be activated upon cell-cell contact with activated T cells resulting in enhanced mast cell degranulation, migration and adhesion to extracellular matrix and endothelial cell ligands [12]. In recent experiments with mice, mast cells and their TNF have been reported to enhance antigen-and Th17 celldependent development of a neutrophil-rich inXammatory response in airways [126] suggesting that mast cells can promote Th17 cell-dependent inXammation in vivo. In addition to local actions in the skin previous Wndings in mice show that as a result of dinitroXuorobenzene-induced contact hypersensitivity mast cells are activated and they migrate to draining lymph nodes wherein they can mediate T cell recruitment [198].…”
Section: Mast Cells In Relation To Cells Of the Immune System In Psormentioning
confidence: 99%